Innovative approach: Teachers’ perceptions of implementation Merdeka Belajar Curriculum in physics education - Alfini Yunita Puteri; Afaurina Indriana Safitri; Yeni Sherliyanti; Innita Fashihatul Qiro’ah; Vinka Amalia Mustafaroh; Setyo Admoko; Suliyanah Suliyanah; Imam Sucahyo (Universitas PGRI Kanjuruhan Malang, 2024)
These various perceptions emerged both positive and negative perceptions regarding the implementation of the latest curriculum, namely the Merdeka Belajar curriculum. The purpose of writing this scientific article is to explore various teachers' perceptions regarding the implementation of the Merdeka Belajar curriculum in physics subjects. The research was conducted at one of the state high schools in the Surabaya area. The approach used in this research is a qualitative approach with a case study method. The data collection technique was carried out using purposive sampling and data triangulation as an analysis technique. This research includes the perceptions of physics teachers regarding the implementation of the Merdeka curriculum. There were positive and negative responses conveyed by the teachers. The shortcomings of the Merdeka curriculum implemented in schools are that teachers are still unable to adapt to the relatively new Merdeka curriculum and there is still a lack of information and references regarding the Merdeka curriculum teaching modules. The solution that can be applied to overcome this problem is that schools must pay more attention to teachers by holding more frequent training activities in preparing learning devices, providing access to training in using technology-based learning support media, and restructuring schedules for implementing P5 activities to be more optimal. The implementation of the Merdeka curriculum in this school has resulted in many teachers' perceptions of creating learning tools that are in accordance with this new curriculum. Apart from that, P5 activities with 12 more hours than other subjects make students take these activities more lightly.